2016
DOI: 10.1016/j.chom.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Metabolites Fuel Host Antibody Responses

Abstract: SUMMARY Antibody production is a metabolically demanding process that is regulated by gut microbiota, but the microbial products supporting B cell responses remain incompletely identified. We report that short-chain fatty acids (SCFAs), produced by gut microbiota as fermentation products of dietary fiber, support host antibody responses. In B cells, SCFAs increase acetyl-CoA and regulate metabolic sensors to increase oxidative phosphorylation, glycolysis and fatty acid synthesis, which produce energy and build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
550
2
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 623 publications
(599 citation statements)
references
References 59 publications
15
550
2
5
Order By: Relevance
“…24 In low SCFA conditions due to low DF consumption, serum antibody and mucosal IgA levels are significantly decreased. 23,25 Germinal center responses in PPs are suppressed in low SCFA conditions but SCFA administration restored antibody production in mice fed a DF-free diet (Fig. 1).…”
Section: Regulation Of Antibody Production By Scfasmentioning
confidence: 94%
See 3 more Smart Citations
“…24 In low SCFA conditions due to low DF consumption, serum antibody and mucosal IgA levels are significantly decreased. 23,25 Germinal center responses in PPs are suppressed in low SCFA conditions but SCFA administration restored antibody production in mice fed a DF-free diet (Fig. 1).…”
Section: Regulation Of Antibody Production By Scfasmentioning
confidence: 94%
“…Recently, we reported that SCFAs support plasma B cell differentiation. 23 SCFA deficiency occurs when DF levels in diet are low or when the microbiota are suppressed by antibiotics or altered due to dysbiosis. In GF mice, the SCFA levels in the colon are decreased to about one percent of normal levels.…”
Section: Regulation Of Antibody Production By Scfasmentioning
confidence: 99%
See 2 more Smart Citations
“…4b). Since the furan-and pyran-like structures of fullerenol NPs appeared similar to those of the polysaccharides in dietary fiber, which is the main nutrient for SCFAs-producing gut bacteria [33], we hypothesize that Fol1 and Fol113 NPs might function like dietary polysaccharides to promote SCFAs-producing bacteria survival.…”
Section: Physicochemical Characterization Of Fullerenol Npsmentioning
confidence: 95%